Entrelaçando antropologia e educação: percepções acerca do acesso e permanência indígena na UNIPAMPA - Silva, Renata Colbeich da (2023)
This study aims to understand Indigenous Higher Education in the Brazilian context, focusing on the experience of Indigenous students at the Federal University of Pampa - Unipampa/RS. Through a multisited ethnographic approach, the study investigated how these students have access and permanence in the institution, identifying policies and practices adopted to promote the inclusion and empowerment of these students. The study also explores how anthropology can contribute to the promotion of the inclusion of Indigenous students in education, analyzing how the perception and learning of these students occur in different cultural and social contexts. Additionally, the study addresses the impacts of the Covid-19 pandemic on Indigenous Higher Education, identifying challenges and opportunities that have arisen in this context.